Microbiome analysis reveals the effects of black soldier fly oil on gut microbiota in pigeon - Liu, Suzhen; Luo, Houqiang; Wang, Meng; Wang, Qingyan; Duan, Longchuan; Han, Qingsong; Sun, Siwei; Wei, Caixia; Jin, Junjie (Frontiers in Microbiology, 2022)
The gut microbiota plays an important role in poultry physiology, immunity and metabolism. Black soldier fly oil is known to have a positive effect on the gut microbiota. However, the specific effect of black soldier fly oil on the composition and structure of the gut microbiota of the pigeon is unknown. In this experiment, 16S rDNA high-throughput sequencing was carried out to study the effect of different doses of black soldier fly oil on the changes of pigeon intestinal microbes. Results indicated that the different doses of black soldier fly oil had no effect on the gut microbial diversity of the pigeon. Although the dominant phyla (Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria) and genus (uncultured_bacterium_f_Lachnospiraceae and Desulfovibrio) in control group and experimental group with different doses were the same, the abundances of some beneficial bacteria (Megasphaera, Intestinimonas, Prevotella_9, Lachnospiraceae_UCG-001, Faecalibacterium, Coprococcus_2, Parabacteroides, Megasphaera, Leuconostoc, Prevotellaceae_UCG-001, Lactococcus, Ruminococcaceae_UCG-014 and Coprococcus_2) increased significantly as the concentration of black soldier fly oil increased. Taken together, this study indicated that black soldier fly oil supplementation could improve gut microbial composition and structure by increasing the proportions of beneficial bacteria. Notably, this is the first report on the effects of black soldier fly oil on the gut microbiota of pigeon, which contribute to understanding the positive effects of black soldier fly oil from the gut microbial perspective.